TET2-mediated 5-hydroxymethylcytosine of TXNIP promotes cell cycle arrest in systemic anaplastic large cell lymphoma - Ziqing Yu; Lihua Zhong; Wangyang Tang; Wenfang Zhang; Ting Lin; Weifeng Zhu; Gang Chen; Jianchao Wang (Clinical Epigenetics)
Abstract Background 5-Hydroxymethylcytosine (5hmC) modification represents a significant epigenetic modification within DNA, playing a pivotal role in a range of biological processes associated with various types of cancer. The role of 5hmC in systemic anaplastic large cell lymphoma (ALCL) has not been thoroughly investigated. This study aims to examine the function of 5hmC in the advancement of ALCL. Methods Formalin-fixed, paraffin-embedded (FFPE) tumor tissues (n = 46) were obtained from ALCL patients. GEO dataset was used to analyze the expression 5hmC-relative enzymes. Immunohistochemistry was conducted to assess the level of 5hmC and Ten-eleven translocation 2 (TET2) on FFPE samples. The ALK-positive cell line, Su-DHL-1, and the ALK-negative cell line, DL-40, were utilized as in vitro experimental models. RNA-sequencing and hMeDIP-sequencing assays were performed to explore the potential functions of TET2 in cell cycle regulation. Results Our study identified a reduction of 5hmC levels in patients with ALCL, which exhibited a positive correlation with TET2 expression. Downregulation TET2 resulted in decreased 5hmC levels and facilitated the progression of the cell cycle in ALCL cell lines. hMeDIP-seq and subsequent functional analyses demonstrated the involvement of thioredoxin interacting protein (TXNIP) in the regulation of ALCL cells. Further mechanistic studies revealed that 5hmC levels influenced TXNIP expression. Conclusions Our study underscores the pivotal roles of 5hmC and TET2 in the regulation of cell cycle progression in ALCL. Therapeutic strategies aimed at targeting 5hmC modification or TET2 may offer a novel approach for the management of ALCL.